MENDIALOGKAN SAINS DAN AGAMA DALAM UPAYA RESOLUSI KONFLIK - Wira Hadikusuma (Institut Agama Islam Negeri Bengkulu, 2017)
The issue of science and religion is a study that never hasbis to be studied and discussed. Both have uniqueness and can be continuously in accordance with the development of the times and science. In its development between science and religion there is a difference among scientists puts the relationship between science and religion, both those who are conflicted and who view the effort to integrate them. In this study can be drawn red thread between the two in an effort mendialogkannya, that religion can be used as a guide and guide for scientists, so that what is produced can work for the welfare of both the world and the hereafter. This is in line with the same scientific and religious objectives for human well-being, so that science and religion are something that can not be separated from one another. Because religion is not interpreted solely by a normative theological approach, it requires an interdisciplinary, multidisciplinary and transdisciplinary approach, so that both have the power to support and mutilate.